2017
DOI: 10.1088/1361-6641/32/2/025014
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of the optical Stark effect in InGaAs/InAlAs quantum dots

Abstract: In this paper, we examine the three-level optical Stark effect of excitons in InGaAs/InAlAs quantum dots using renormalized wavefunction formulation. The system was assumed to be irradiated by two lasers in which a strong laser dynamically couples electron-quantized levels, while a weaker laser probes interband absorption. Our results show that, in the presence of the resonant strong laser, two new absorption peaks of excitons appear in the absorption spectrum as a clear indication of the effect. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 39 publications
4
20
0
1
Order By: Relevance
“…This reduction is the consequence of the conservation of the electronic transition rate as discussed in Ref. [11]. In short, the above results demonstrate the existence of the threelevel optical Stark effect of exciton in the prolate ellipsoidal quantum dots.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…This reduction is the consequence of the conservation of the electronic transition rate as discussed in Ref. [11]. In short, the above results demonstrate the existence of the threelevel optical Stark effect of exciton in the prolate ellipsoidal quantum dots.…”
Section: Resultssupporting
confidence: 71%
“…Quantum dot structures have many interesting applications, such as producing artificial atoms and molecules [5], single-electron transistors [6], and quantum dot lasers [7]. In recent years, there has seen many studies on optical properties in quantum dots with different shapes, for example, cylindrical, cubic, and spherical quantum dots [8][9][10][11][12]. These studies show that optical properties of quantum dots are highly dependent on external fields and size of quantum dots.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, we see that the absorption spectra of the excitons shift to a lower energy region as the wire radius becomes larger. It is worth mentioning that we have applied our theory for the other low-dimensional structures such as quantum dots and quantum wells and we have obtained the similar results [55,56]. Journal of Nanomaterials…”
Section: Journal Of Nanomaterialssupporting
confidence: 56%
“…We also found that, in Figure 2, the intensity of the exciton absorption spectra in the case of without pump wave (dashed line) appears much higher than that in the presence of the pump wave (solid line). This reduction is due to the act of the conservation of the transition rate [55]. We realize that, by turning the pump laser on or off, this effect can control the system to work as an optical switching by letting the probe laser beam of certain frequency propagate through it or not.…”
Section: Resultsmentioning
confidence: 99%